Adaptind the US Main Street Philosophy and Program to the Romanian Urban Context. Could it Possibly Work? - Bogdana NEAMTU; Cristina Ramona LEUCA (Transylvanian Review of Administrative Sciences, 2006)
The analysis herein explores the topic of downtown revitalization and focuses on a specific strategy, namely the Main Street approach, as a venue for addressing physical decay, business retention, and historic preservation within small cities/communities throughout the entire US. The paper also addresses how the main street philosophy could be used to deal with urban problems in a completely different setting – Romanian cities – and which would be the steps Romanian public authorities at both the central and local level need to undertake in order to implement a Main Street Program in Romania. The paper has a threefold structure. In the first section the focus is on the US urban context. A brief analysis of the causes that have generated the decline of downtowns and their commercial/business districts is provided. It is underscored that cities are not merely the passive recipients of change; rather decision-makers have the ability to make choices that maximize the assets the community has while minimizing the obstacles they face. The Main Street program implemented by the National Trust for Historic Preservation is described as one possible strategy aiming at the revitalization of downtowns and commercial/business districts. The focus is on assessing how such a strategy responds to the challenges downtowns face. The Main Street approach is then compared and contrasted against other possible downtown redevelopment strategies. In the second part of the paper the focus shifts from the US context to Romanian cities. A brief analysis of the problems Romanian municipalities face with regard to downtowns is provided. The authors argue that the main street approach is relevant and worth taking into consideration as a counterpoint to urban sprawl - (increase in the number of retailers and malls at the outskirts of the urban cores, decline of open space and opportunities for leisure in the downtown, increase in the number of suburban single family residences, etc) - that could possibly affect the vitality of Romanian downtowns on the long term. A framework for the implementation of a main street program in the context of Romanian cities is proposed and described.